Diabetic Foot Ulcers: Impact on Quality of Life and Instruments for Its Measurement - Qomariyanti, Khairunisa; Sauriasari, Rani; Sartika, Ratu Ayu Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Diabetic foot ulcers (DFUs) are a major complication of diabetes mellitus, significantly impacting patients' quality of life (QoL) due to the heightened risk of infection and amputation. Pharmacists play a crucial role in managing diabetes and its complications, and assessing QoL can be a valuable tool for monitoring treatment success and medication effectiveness. This review explores instruments used to measure QoL in patients with DFUs, encompassing both general and disease-specific tools. We examine the impact of DFUs on QoL and discuss various theoretical frameworks used to understand this complex relationship.